2001
DOI: 10.4269/ajtmh.2001.64.187
|View full text |Cite
|
Sign up to set email alerts
|

Treatment failure in children in a randomized clinical trial with 10 and 20 days of meglumine antimonate for cutaneous leishmaniasis due to Leishmania viannia species.

Abstract: Abstract. Clinical response to supervised treatment of Colombian patients with cutaneous leishmaniasis was evaluated in a randomized controlled trial comparing 10 days versus 20 days of treatment with meglumine antimonate (20 mg Sb/kg/day). Masked examiners evaluated clinical response defined as 100% re-epithelialization of all lesions at 13 weeks and no relapses during 52 weeks of follow-up. The efficacy of meglumine antimonate for 10 days' treatment was 61% (28 of 46) compared to 67% (24 of 36) for 20 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
2
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 30 publications
7
79
2
11
Order By: Relevance
“…2 In CL, the efficacy of antimonials varies: 94.2% in Bolivia, 3 84% in Brazil, 4 75.6-78% in Peru, 5,6 and 61-67% in Colombia. 7 The efficacy of pentamidine is 35% in Peru. 6 Other treatments have been used, such as amphotericin B as a first-or second-line treatment to cure VL, MCL, and CL.…”
Section: Introductionmentioning
confidence: 99%
“…2 In CL, the efficacy of antimonials varies: 94.2% in Bolivia, 3 84% in Brazil, 4 75.6-78% in Peru, 5,6 and 61-67% in Colombia. 7 The efficacy of pentamidine is 35% in Peru. 6 Other treatments have been used, such as amphotericin B as a first-or second-line treatment to cure VL, MCL, and CL.…”
Section: Introductionmentioning
confidence: 99%
“…In the New World, the efficacy of anti monials for the treatment of cutaneous leishmaniasis has been variable. In Bolivia, treatment failure was observed in 7% of patients [78], in 16% in Brazil [79], and in 39% of patients in Colombia [80]. In the Old World, failure of this drug is approximately 13%, and this drug is considered as satisfactory for the treatment of cutaneous leishmaniasis.…”
Section: First-line Drugsmentioning
confidence: 99%
“…The few studies that have been conducted have shown that children with CL have a lower response rate to pentavalent antimonial compounds and a significantly higher elimination rate of antimony compared with adults. 1,2 These circumstances coupled with the logistic, social, and economic barriers to access and adherence to 20 days of intramuscular injections limit the effectiveness of antimonial drugs, which remain the first-line treatment of CL in children. Miltefosine has recently been shown to be non-inferior to meglumine antimoniate in the treatment of pediatric CL in Colombia, 3 and its efficacy in children is corroborated by clinical trials in populations where Leishmania guyanensis and L. braziliensis are endemic in Brazil.…”
Section: Introductionmentioning
confidence: 99%